2016
DOI: 10.1371/journal.pone.0152741
|View full text |Cite
|
Sign up to set email alerts
|

Memantine before Mastectomy Prevents Post-Surgery Pain: A Randomized, Blinded Clinical Trial in Surgical Patients

Abstract: BackgroundNeuropathic pain following surgical treatment for breast cancer with or without chemotherapy is a clinical burden and patients frequently report cognitive, emotional and quality of life impairment. A preclinical study recently showed that memantine administered before surgery may prevent neuropathic pain development and cognitive dysfunction. With a translational approach, a clinical trial has been carried out to evaluate whether memantine administered before and after mastectomy could prevent the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
1
40
0
3
Order By: Relevance
“…The mechanisms involved in NP are complex and involve both peripheral and central pathophysiological phenomenon, cross talk between A and C fibers and sensitization after injury, formation of ectopic neuronal pacemakers with abnormal or dysfunctional sodium channels, expression of novel ion channels or receptors, activation of several signaling pathways that mediate the induction and maintenance of NP through transcriptional and posttranslational mechanisms. 3 NP negatively impacts the quality of life and aggravates functional decline. 4 , 5 It is characterized by clinical manifestations that are present across different NP conditions, and its prevalence is nearly 10% in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in NP are complex and involve both peripheral and central pathophysiological phenomenon, cross talk between A and C fibers and sensitization after injury, formation of ectopic neuronal pacemakers with abnormal or dysfunctional sodium channels, expression of novel ion channels or receptors, activation of several signaling pathways that mediate the induction and maintenance of NP through transcriptional and posttranslational mechanisms. 3 NP negatively impacts the quality of life and aggravates functional decline. 4 , 5 It is characterized by clinical manifestations that are present across different NP conditions, and its prevalence is nearly 10% in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, memantine has been shown to be a successful option to prevent pain and pain-associated psychological impairment. Preclinical findings showed that central sensitization was aborted by giving memantine a few days before surgery in an NP model of spinal nerve ligation [37], and was confirmed in patients undergoing mastectomy [72]. The suggestion that memantine may induce sensori-limbic dissociation, to explain the paradox of presence of NP and patients' indifference to it, gives this drug a supplementary property, protecting not only against pain sensitization but also against pain-induced emotional alteration.…”
Section: Discussionmentioning
confidence: 96%
“…Morel et al ( 15 ) examined the effect of memantine on the reduction of postoperative pain in mastectomy. In this study, memantine was administered at a dose of 5 to 20 mg daily after mastectomy for two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that memantine is able to prevent postoperative pain if administered prior to nerve injuries. However, it is crucial to carry out further RCT studies in homogeneous groups of patients to explore the therapeutic potential of memantine for relieving postoperative pain ( 9 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%